Silicon nitride powder and method for producing silicon nitride sintered compact

A silicon nitride powder with controlled β conversion and amorphous ratios, produced by combining specific types and processing methods, addresses inconsistencies in sintered body quality, achieving superior mechanical properties and stability.

JP2025018537APending Publication Date: 2025-02-06TOKUYAMA CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023122325
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Existing silicon nitride powders exhibit variations in physical properties and mechanical strength, leading to inconsistent quality in sintered bodies, particularly when high β conversion rates and amorphous content are not adequately controlled.

Method used

A silicon nitride powder with a β conversion rate of 98% or more and an amorphous content of 1-60%, preferably 3-55%, is produced by combining amorphous and crystalline silicon nitride powders, optimized through ball milling and combustion synthesis, to achieve a bimodal particle structure that enhances mechanical properties and stability.

Benefits of technology

The resulting silicon nitride sintered bodies exhibit high fracture toughness, three-point bending strength, and thermal conductivity with minimal variations, ensuring excellent quality stability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018537000001
    Figure 2025018537000001
Patent Text Reader

Abstract

To provide a silicon nitride powder capable of producing a silicon nitride sintered compact having superior mechanical properties, with little variation in physical properties and good quality stability.SOLUTION: A silicon nitride powder includes a β phase fraction of 98% or more and an amorphous fraction of 1 to 60%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silicon nitride powder and a method for producing a silicon nitride sintered body using the same. [Background technology]

[0002] Silicon nitride powder has attracted attention as a ceramic raw material for various industrial materials because its sintered body has excellent properties such as high thermal conductivity, high insulation and high strength. Known methods for producing silicon nitride powder include, for example, the reduction-nitridation method, in which silica powder is used as the raw material and nitrogen gas is passed through in the presence of carbon powder to produce silicon nitride, the direct nitridation method, in which silicon powder is reacted with nitrogen at high temperatures, and the imide decomposition method, in which silicon halide is reacted with ammonia.

[0003] It is known that silicon nitride powder has different particle size distributions and different crystal morphologies depending on the above-mentioned production methods. Silicon nitride powder has two crystal morphologies, α-type and β-type, and the sinterability and the like differs depending on the crystal morphology. Therefore, the relationship between the crystal morphology of silicon nitride powder and the physical properties of the sintered body has been extensively studied.

[0004] Patent Document 1 discloses an invention relating to silicon nitride powder characterized by a β-phase content of 50% or more and an amorphous component content of 5 to 50% by weight. In the examples, it shows that silicon nitride powder with a β-phase ratio of 54 to 96% has been synthesized, and describes that the use of this synthetic silicon nitride powder results in a silicon nitride sintered body with excellent sinterability and high reliability.

[0005] In Patent Document 2, 29 The amorphous fraction measured by magic angle spinning nuclear magnetic resonance spectroscopy of Si nuclei is 6.5 to 18 wt%, the α phase fraction is 70 to 93.5 wt%, and the β phase fraction is 23.5 wt% or less. The specific surface area is 5 to 25 m 2The invention discloses a silicon nitride powder having a specific surface area of ​​100 nm to 150 nm / g, and describes that the silicon nitride powder enables the stable production of highly tough and reliable silicon nitride ceramics with good reproducibility. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-64907 [Patent Document 2] Japanese Patent Application Publication No. 11-171512 Summary of the Invention [Problem to be solved by the invention]

[0007] The silicon nitride powders described in Patent Documents 1 and 2 above can produce sintered bodies with high strength, but the physical properties tend to vary greatly between samples, and there is room for improvement in terms of producing silicon nitride sintered bodies with good quality stability. In the examples of Patent Document 1, a synthetic silicon nitride powder with a β-phase ratio (β-phase ratio) of 54 to 96% is obtained, and the variation in four-point bending strength at room temperature is evaluated, but no evaluation is performed in the range of extremely high β-phase ratio. Moreover, the silicon nitride powder of Patent Document 2 has a β-phase fraction (β-phase ratio) of 23.5% by weight or less, and is an invention premised on a silicon nitride powder with a low β-phase ratio. Thus, the physical properties of silicon nitride powder containing amorphous silicon nitride and having an extremely high β-phase ratio have not been investigated in detail.

[0008] An object of the present invention is to provide a silicon nitride powder which can be used to produce silicon nitride sintered bodies which have excellent mechanical properties, little variation in physical properties, and good quality stability. [Means for solving the problem]

[0009] The present inventors have conducted extensive research in order to achieve the above object, and have discovered that the above problems can be solved by a silicon nitride powder having an extremely high β-phase ratio and an amorphous ratio within a specific range, thereby completing the present invention.

[0010] The gist of the present invention is the following [1] to [4]. [1] Silicon nitride powder having a β-phase rate of 98% or more and an amorphous rate of 1 to 60%. [2] The silicon nitride powder according to the above item [1], which is a mixed silicon nitride powder containing an amorphous silicon nitride powder A and a crystalline silicon nitride powder B, wherein the amorphous silicon nitride powder A is a ball milled product of a crystalline silicon nitride powder. [3] The silicon nitride powder according to [1] or [2] above, which is for sintering. [4] A method for producing a silicon nitride sintered body, comprising at least a step of sintering the silicon nitride powder described in [3] above to obtain a silicon nitride sintered body. Effect of the Invention

[0011] According to the present invention, there is provided a silicon nitride powder capable of producing a silicon nitride sintered body having excellent mechanical properties, little variation in physical properties, and good quality stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Silicon nitride powder] The silicon nitride powder of the present invention has a β-phase rate of 98% or more and an amorphous rate of 1 to 60%. The silicon nitride powder of the present invention is preferably used for sintering, and the silicon nitride sintered body obtained by sintering has high mechanical properties, little variation in physical properties, and excellent quality stability. The reason for this is unclear, but it is presumed that when the β-phase rate of the silicon nitride powder is 98% or more and the amorphous rate is 1 to 60%, the resulting silicon nitride sintered body is more likely to form a so-called bimodal structure formed by silicon nitride particles with relatively large particle sizes and silicon nitride particles with relatively small particle sizes, resulting in improved mechanical properties. In addition, the high β-phase rate of the silicon nitride powder reduces the variation in the physical properties of the resulting silicon nitride sintered body, improving quality stability. This is thought to be because proper grain growth is promoted by preventing abnormal grain growth caused by α-type silicon nitride powder.

[0013] In this specification, silicon nitride powder with a β-phase rate of 50% or more may be referred to as β-type silicon nitride powder, and silicon nitride powder with an α-phase rate of 50% or more may be referred to as α-type silicon nitride powder.

[0014] <Amorphous ratio> The amorphous rate of the silicon nitride powder of the present invention is 1 to 60%. When the amorphous rate of the silicon nitride powder is 1% or more, the mechanical properties such as fracture toughness and three-point bending strength of the obtained silicon nitride sintered body tend to be improved. When the amorphous rate of the silicon nitride powder is more than 60%, the silicon nitride sintered body tends to crack during firing. From the viewpoint of improving the mechanical properties of the silicon nitride sintered body and reducing the variation in physical properties, the amorphous rate of the silicon nitride powder is preferably 3 to 55%, more preferably 15 to 50%, and further preferably 20 to 30%. The method for adjusting the amorphous ratio of the silicon nitride powder is not particularly limited, but an example thereof includes a method of using a silicon nitride mixed powder containing amorphous silicon nitride powder A and crystalline silicon nitride powder B as described below, and adjusting the content of each powder.

[0015] The amorphous ratio is calculated by measuring the crystallinity X (%) of the silicon nitride powder and using the following formula: Amorphous rate of silicon nitride powder (%) = 100 - crystallinity x The crystallinity X of silicon nitride powder is determined by X-ray diffraction measurement. Specifically, it is calculated by the following formula from the total crystalline peak area (Sc), which is the sum of the integrated intensities of each crystalline peak, and the area of ​​the amorphous halo (Sa), which is the integrated intensity of the amorphous halo, measured by X-ray diffraction measurement. Crystallinity X(%)=Sc / (Sc+Sa)×100 Details of the method for measuring the crystallinity X of the silicon nitride powder are as described in the Examples.

[0016] <β conversion rate> The β-phase ratio of the silicon nitride powder of the present invention is 98% or more. If the β-phase ratio of the silicon nitride powder is less than 98%, the physical properties of the resulting silicon nitride sintered body tend to vary widely and the quality stability tends to decrease. From the viewpoint of reducing the variation in the physical properties of the resulting silicon nitride sintered body, the β-phase ratio of the silicon nitride powder is preferably 98.5% or more, more preferably 99% or more. The upper limit of the β-phase ratio is 100%.

[0017] The β-phase ratio means the peak intensity ratio of the β-phase to the total of the α-phase and β-phase in the silicon nitride powder [100 × (peak intensity of the β-phase) / (peak intensity of the α-phase + peak intensity of the β-phase)], and is obtained by powder X-ray diffraction (XRD) measurement using CuKα rays. More specifically, it is obtained by calculating the weight ratio of the α-phase and β-phase in the silicon nitride powder according to the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780.

[0018] <Amorphous silicon nitride powder A> The silicon nitride powder of the present invention is preferably a mixed silicon nitride powder containing amorphous silicon nitride powder A and crystalline silicon nitride powder B. By containing amorphous silicon nitride powder A, it is easy to adjust the amorphous ratio of the silicon nitride powder to a desired range.

[0019] The amorphous silicon nitride powder A is a silicon nitride powder having a crystallinity of 50% or less as calculated by X-ray diffraction measurement. From the viewpoint of improving the mechanical strength of the resulting silicon nitride sintered body, the crystallinity of the amorphous silicon nitride powder A is preferably 10% or less, more preferably 5% or less. The lower limit of the crystallinity of the amorphous silicon nitride powder A is 0%.

[0020] The method for producing the amorphous silicon nitride powder A is not particularly limited, but may be obtained by applying a method that easily produces amorphous silicon nitride, such as an imide decomposition method, or may be obtained by amorphizing crystalline silicon nitride powder. In particular, from the viewpoint of improving the mechanical strength of the resulting sintered body, it is preferable that the amorphous silicon nitride powder A is obtained by amorphizing crystalline silicon nitride powder. The amorphization is preferably performed by ball milling. That is, the amorphous silicon nitride powder A is preferably a ball milled product of crystalline silicon nitride powder. The details of the method for producing the amorphous silicon nitride powder A will be described later.

[0021] The content of amorphous silicon nitride powder A in the silicon nitride mixed powder is preferably 1 to 60 mass %, more preferably 3 to 55 mass %, further preferably 15 to 50 mass %, and further preferably 20 to 30 mass %. When the content of the amorphous silicon nitride powder A is within this range, the amorphous ratio of the silicon nitride powder can be easily adjusted to the desired range described above.

[0022] <Crystalline silicon nitride powder B> The silicon nitride mixed powder contains crystalline silicon nitride powder B. Crystalline silicon nitride powder is silicon nitride powder having a crystallinity of more than 96% as calculated by X-ray diffraction measurement. The crystallinity of crystalline silicon nitride powder B is preferably 98% or more, more preferably 99% or more, from the viewpoint of improving the mechanical strength of the resulting silicon nitride sintered body.

[0023] The β-phase ratio of the crystalline silicon nitride powder B is preferably 98% or more, more preferably 98.5% or more, and even more preferably 99% or more. The upper limit of the β-phase ratio of the crystalline silicon nitride powder B is 100%. When the β-phase ratio of the crystalline silicon nitride powder B is within this range, the β-phase ratio of the silicon nitride powder of the present invention can be easily adjusted to the desired range described above.

[0024] The average particle size of the crystalline silicon nitride powder B is not particularly limited, but from the viewpoint of improving the mechanical strength of the resulting silicon nitride sintered body, it is preferably 0.3 to 2.0 μm, and more preferably 0.6 to 1.0 μm. In this specification, the average particle size can be measured by a laser diffraction / scattering particle size distribution analyzer, and a volume frequency distribution curve is obtained with the horizontal axis representing particle size (μm) and the vertical axis representing volume frequency. The particle size (D50) at which the cumulative curve of the measured volume-based particle size distribution becomes 50% is defined as the average particle size.

[0025] The method for producing the crystalline silicon nitride powder B is not particularly limited, and any known production method can be used. However, from the viewpoint of easily obtaining a powder with a high β content, it is preferable to use a direct nitriding method such as a combustion synthesis method.

[0026] The content of the crystalline silicon nitride powder B in the silicon nitride mixed powder is preferably 40 to 99 mass%, more preferably 45 to 97 mass%, even more preferably 50 to 85 mass%, and still more preferably 70 to 80 mass%. When the content of silicon nitride powder B is within this range, the amorphous ratio of the silicon nitride powder of the present invention can be easily adjusted to the desired range described above.

[0027] [Method of manufacturing sintered silicon nitride] The silicon nitride sintered body obtained by sintering the silicon nitride powder of the present invention has excellent mechanical properties, little variation in physical properties, and excellent quality stability. The method for producing the silicon nitride sintered body will be described below. The method for producing a silicon nitride sintered body of the present invention comprises at least a step of sintering the above-mentioned silicon nitride powder to obtain a silicon nitride sintered body.

[0028] In the method for producing a silicon nitride sintered body of the present invention, when a silicon nitride mixed powder is used as the silicon nitride powder, the silicon nitride mixed powder is first produced as described above, and then the silicon nitride mixed powder is fired to obtain a silicon nitride sintered body. This will be described in detail below.

[0029] <Production of silicon nitride mixed powder> The method for producing the mixed silicon nitride powder is not particularly limited, but a method in which amorphous silicon nitride powder A and crystalline silicon nitride powder B are separately prepared and then mixed is preferred.

[0030] (Production of amorphous silicon nitride powder A) The method for producing the amorphous silicon nitride powder A is not particularly limited, but may be selected from a method that is easy to obtain amorphous silicon nitride powder, such as the imide decomposition method, or may be obtained by amorphizing crystalline silicon nitride powder. Among them, from the viewpoint of improving the mechanical strength of the obtained sintered body and from the viewpoint of safety during production, it is preferable that the amorphous silicon nitride powder A is obtained by amorphizing crystalline silicon nitride powder, and more specifically, it is preferable that the amorphous silicon nitride powder A is a ball milled product of crystalline silicon nitride powder.

[0031] Amorphous silicon nitride powder can be obtained by ball milling crystalline silicon nitride powder. The crystal form of the crystalline silicon nitride powder to be ball milled is not particularly limited, and may be high or low β-phase. However, from the viewpoint of reducing the amount of dissolved oxygen in the obtained sintered body and increasing the thermal conductivity, a high β-phase (e.g., β-phase of 98% or more) is preferable. Therefore, it is also preferable to use crystalline silicon nitride powder B as the crystalline silicon nitride powder to be ball milled.

[0032] The ball mill used in the ball milling process is not particularly limited, and a planetary ball mill, a vibrating ball mill, a rolling ball mill, a stirring ball mill, etc. can be used. Among these, a planetary ball mill is preferred from the viewpoint of obtaining the desired amorphous silicon nitride powder A and improving the mechanical properties of the silicon nitride sintered body. The use of a planetary ball mill allows silicon nitride powder to be processed by the centrifugal force generated by the rotation and revolution motion. More specifically, crystalline silicon nitride powder and balls are introduced into a cylindrical mill container equipped with a planetary ball mill, and the cylindrical mill container is rotated on its axis while revolving around another axis parallel to the rotation axis, thereby applying the centrifugal acceleration of the rotation and revolution to the silicon nitride powder and balls in the mill container, thereby obtaining amorphous silicon nitride powder. The rotation speed of the planetary ball mill is preferably 250 to 410 rpm, more preferably 330 to 370 rpm. The material of the balls used is not particularly limited, but from the viewpoint of reducing the amount of impurities in the ball milled product obtained, silicon nitride-based balls are preferred. The treatment time is not particularly limited, but is preferably 6 to 30 hours, more preferably 12 to 24 hours.

[0033] (Production of crystalline silicon nitride powder B) The method for producing the crystalline silicon nitride powder B is not particularly limited, and known methods such as reduction nitridation and direct nitridation methods such as combustion synthesis can be applied, but the combustion synthesis method is preferred because it is easy to obtain silicon nitride powder with a high β-content.

[0034] The combustion synthesis method is a method for producing silicon nitride powder by igniting raw material powder containing silicon powder and propagating the heat of nitriding combustion generated by the nitriding reaction of the silicon powder throughout the raw material powder. The conditions for the combustion synthesis are not particularly limited, and the synthesis can be carried out under general conditions. For example, a raw powder mixture of silicon powder and silicon nitride powder as a diluent is filled into a reaction vessel, and the end of the raw powder is ignited to carry out a combustion synthesis reaction, thereby obtaining a lump product made of silicon nitride. The content of the diluent is not particularly limited, but can be, for example, 5 to 50 mass%, more preferably 10 to 30 mass%, based on the total amount of the raw powder. The inside of the reactor is generally under a nitrogen atmosphere. The reaction may be carried out under normal pressure or under pressure, but is preferably carried out under pressure. The aggregate product obtained by the combustion synthesis reaction as described above can be mechanically pulverized by a known pulverizer to obtain crystalline silicon nitride powder B having an appropriate particle size distribution.

[0035] (Mixing amount) The amorphous silicon nitride powder A produced as described above can be mixed with the crystalline silicon nitride powder B to obtain a silicon nitride mixed powder. In this case, the amount of the amorphous silicon nitride powder A and the crystalline silicon nitride powder B used may be appropriately adjusted so that the amorphous rate of the silicon nitride mixed powder is 1 to 60%. Specifically, the content of the amorphous silicon nitride powder A and the content of the crystalline silicon nitride powder B in the silicon nitride mixed powder may be appropriately adjusted and mixed so that they are within the ranges described above.

[0036] (Firing) The silicon nitride powder mixture produced as described above can then be fired to obtain a silicon nitride sintered body. The firing method is not particularly limited, and any known method can be used. For example, it is preferable to prepare a mixed raw material by mixing a silicon nitride powder mixture with a sintering aid, and then mold the mixed raw material into a desired shape and sinter it. The method for molding the mixed raw material is not particularly limited, but for example, press molding can be used. As the press molding, uniaxial press molding is representative, but a method of performing CIP (Cold Isostatic Pressing) molding after uniaxial press molding is preferably used. The sintering aid is not particularly limited, but examples thereof include yttria, magnesia, zirconia, and alumina. The sintering aid may be used alone or in combination of two or more. The content of the sintering aid in the mixed raw material is not particularly limited, but is preferably 1 to 15 parts by mass, more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the silicon nitride mixed powder.

[0037] The firing is preferably carried out in an inert gas atmosphere, such as a nitrogen atmosphere or an argon atmosphere. The firing may be performed under normal pressure or under pressure at a firing temperature of, for example, 1200 to 2000°C, and preferably 1500 to 1900°C.

[0038] <Sintered silicon nitride> The silicon nitride sintered body obtained from the silicon nitride powder of the present invention has excellent mechanical properties. The fracture toughness value of the silicon nitride sintered body of the present invention is preferably 6.0 MPa m 1 / 2 More preferably, it is 6.5 MPa m 1 / 2 More preferably, it is 6.7 MPa m 1 / 2 The upper limit of the fracture toughness value is not particularly limited, but is, for example, 15 MPa m 1 / 2 It is. The three-point bending strength of the silicon nitride sintered body of the present invention is preferably 550 MPa or more, more preferably 580 MPa or more, and further preferably 600 MPa or more. The upper limit of the three-point bending strength is not particularly limited, but is, for example, 1000 MPa.

[0039] The silicon nitride sintered body of the present invention has small variations in physical properties. Therefore, for example, the standard deviation of the above-mentioned three-point bending strength is preferably 80 MPa or less, more preferably 70 MPa or less, and even more preferably 40 MPa or less. The lower the standard deviation of the three-point bending strength, the better, and ideally it is 0 MPa.

[0040] The thermal conductivity of the silicon nitride sintered body of the present invention is not particularly limited, but from the viewpoint of improving heat dissipation, it is preferably 70 W / mK or more, more preferably 75 W / mK or more, and even more preferably 80 W / mK or more. The upper limit of the thermal conductivity is not particularly limited, but is, for example, 150 W / mK.

[0041] The fracture toughness, three-point bending strength, standard deviation of the three-point bending strength, and thermal conductivity of the silicon nitride sintered body are determined by the methods described in the Examples.

[0042] As described above, the silicon nitride powder of the present invention has a β-phase rate and an amorphous rate within specific ranges, and therefore the silicon nitride sintered body obtained by sintering the powder has excellent mechanical properties, little variation in physical properties, and excellent quality stability. EXAMPLES

[0043] EXAMPLES The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0044] [Measurement method] Various physical properties in the examples and comparative examples were measured by the following methods.

[0045] (1) Amorphous ratio The amorphous ratio of the silicon nitride powder was calculated by measuring the crystallinity X (%) of the silicon nitride powder and using the following formula. Amorphous rate of silicon nitride powder (%) = 100 - crystallinity x The crystallinity X was measured as follows.

[0046] (Measurement of Crystallinity X) The crystallinity X of the silicon nitride powder was measured by X-ray diffraction measurement. The X-ray diffraction device used was a JED-3500 manufactured by JEOL Ltd., and the diffraction intensity was measured under the following conditions. Target: Copper (Cu-Kα) Monochromatization: Flat graphite monochromator Tube voltage-tube current: 40kV-400mA X-ray incidence method: Symmetric reflection method (powder method) ·X-ray incident angle (θ): θ-2θ linked Divergence slit width: 0.1mm Receiving slit width: 0.2 mm Detector: Scintillation counter Measurement angle (2θ) range: 10~90° Step angle: 0.04 degrees Counting time: 2.0 seconds The X-ray diffraction intensity curve obtained under the above measurement conditions was separated into an amorphous peak and each crystalline peak by a general peak separation method using a Gaussian function and a Lorentz function using the general peak separation program, which is software provided with the instrument. It was calculated from the total crystalline peak area (Sc), which is the sum of the integrated intensities of each crystalline peak, and the area of ​​the amorphous halo (Sa), which is the integrated intensity of the amorphous halo, according to the following formula. Crystallinity X(%)=Sc / (Sc+Sa)×100

[0047] (2) Beta conversion rate The β-phase ratio of the silicon nitride powder was determined by carrying out X-ray diffraction measurement under the same conditions as in the measurement of the amorphous ratio described above in (1) above, and then calculating the weight ratio of the α phase and β phase of the silicon nitride powder in accordance with the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780, and using the following formula. β phase ratio = 100 × (β phase peak strength) / (α phase peak strength + β phase peak strength) The alpha conversion rate of the crystalline silicon nitride powder (alpha type) used in the comparative examples was calculated by the following formula. Alpha phase ratio = 100 × (alpha phase peak strength) / (alpha phase peak strength + beta phase peak strength)

[0048] (3) Three-point bending strength Test pieces for measuring three-point bending strength were cut out from the silicon nitride sintered bodies produced in each Example and Comparative Example, and the three-point bending strength (MPa) was measured according to a method conforming to ISO 23242:2020. A test jig with a support distance of 15 mm was used. The average value of the three-point bending strengths of the 10 test pieces was taken as the three-point bending strength of the sintered body.

[0049] (4) Fracture toughness Fracture toughness value of sintered silicon nitride (MPa m 1 / 2 ) was calculated by the IF method from the Vickers hardness measured using a Vickers hardness tester AVK-CO manufactured by Akashi Corporation in accordance with the method specified in JIS R1607:2015.

[0050] (5) Density The density of the silicon nitride sintered body was measured using an automatic pycnometer (DMA-220H type, manufactured by Shinko Denshi Co., Ltd.), and the average value of 15 pieces was taken as the density of the silicon nitride sintered body.

[0051] (6) Thermal conductivity Thermal conductivity is calculated by multiplying the thermal diffusivity, density, and specific heat of the silicon nitride sintered body. The specific heat of the silicon nitride sintered body was set to 0.68 (J / g K). The density of the silicon nitride sintered body was set to the value measured in (5). The thermal diffusivity of the silicon nitride sintered body was measured using a laser flash method thermal property measuring device (Kyoto Electronics Manufacturing Co., Ltd.: LFA-502). The density and thermal diffusivity were calculated as the average values ​​of three test pieces.

[0052] (7) Evaluation of variation in physical properties From the three-point bending strength data (data from 10 test pieces) obtained in (3) above, the standard deviation was calculated to evaluate the variation in physical properties.

[0053] <Example 1> (Production of crystalline silicon nitride powder (β type)) Silicon powder was mixed with silicon nitride powder as a diluent to obtain raw powder (Si: 80 mass%, Si 3 N 4A raw material powder layer was obtained. The raw material powder was filled into a reaction vessel to form a raw material powder layer. The reaction vessel was then placed in a pressure-resistant sealed reactor equipped with an ignition device and a gas supply / exhaust mechanism, and the reactor was depressurized to degas it, and then nitrogen gas was supplied to replace the atmosphere. Nitrogen gas was then gradually supplied until the pressure reached 0.7 MPa. The bulk density of the raw material powder at the time when the predetermined pressure was reached (at the time of ignition) was 0.5 g / cm. 3 Thereafter, the edge of the raw material powder in the reaction vessel was ignited, and a combustion synthesis reaction was carried out, resulting in a lump product made of silicon nitride. The obtained aggregated product was crushed to about 5 to 20 μm by rubbing against each other, and then an appropriate amount was put into a vibration mill and finely pulverized for 6 hours. The fine pulverizer and fine pulverization method used were of the usual type, but the inside of the pulverizer was lined with urethane to prevent heavy metal contamination, and balls mainly made of silicon nitride were used as the pulverization media. Also, 1% by mass of ethanol was added as a pulverization aid just before the start of pulverization, and the pulverizer was sealed to perform fine pulverization, obtaining silicon nitride powder. The obtained silicon nitride powder was a crystalline silicon nitride powder (β type) with a crystallinity of 100%, a β rate of 100%, and an average particle size of 1.0 μm.

[0054] (amorphous silicon nitride powder) 8 g of the crystalline silicon nitride powder (β type) produced as described above and silicon nitride balls (diameter 10 mm) were introduced into a cylindrical mill container (made of silicon nitride) of a planetary ball mill (Fritsch Japan "P-5 Classic Line"). The rotation speed was adjusted to 350 rpm, and the crystalline silicon nitride powder was processed for 24 hours to produce amorphous silicon nitride powder. The crystallinity of the amorphous silicon nitride powder was 1%.

[0055] 5 parts by mass of the amorphous silicon nitride powder prepared as above and 95 parts by mass of the crystalline silicon nitride powder (β type) were mixed to obtain 100 parts by mass of a silicon nitride mixed powder. The β-type rate of the silicon nitride mixed powder was 100%. Next, yttria (Y2 O 3 A mixed raw material was prepared by mixing 5 parts by mass of sintered silicon nitride (SnO) and 4 parts by mass of magnesia (MgO), which was then subjected to uniaxial press molding and CIP molding, and then fired at 1780°C for 9 hours in a nitrogen atmosphere at normal pressure to obtain a silicon nitride sintered body. Various evaluations were performed on the silicon nitride sintered body.

[0056] <Examples 2 to 4, Comparative Example 1> Except for changing the amounts of amorphous silicon nitride powder and crystalline silicon nitride powder (β type) in the silicon nitride mixed powder as shown in Table 1, silicon nitride sintered bodies were produced in the same manner as in Example 1 and various evaluations were performed.

[0057] <Example 5, Comparative Example 2> A silicon nitride mixed powder was obtained by mixing amorphous silicon nitride powder, crystalline silicon nitride powder (β type), and crystalline silicon nitride powder (α type) in the proportions shown in Table 1. Note that silicon nitride powder "9FWS" manufactured by Denka Co., Ltd. was used as the crystalline silicon nitride powder (α type). Then, a silicon nitride sintered body was produced in the same manner as in Example 1, and various evaluations were performed.

[0058] [Table 1]

[0059] The results of each example show that the silicon nitride sintered body obtained by sintering the silicon nitride powder of the present invention had high fracture toughness and three-point bending strength, and had excellent mechanical properties. Furthermore, the silicon nitride sintered body of each example had little variation in physical properties and excellent quality stability. In contrast, in Comparative Example 1, which is an example in which no amorphous silicon nitride powder was blended, the obtained silicon nitride sintered body had low fracture toughness and three-point bending strength values ​​and was poor in mechanical properties. Furthermore, in Comparative Example 2, which is an example in which the β-phase ratio of the silicon nitride powder was low, the physical properties of the obtained silicon nitride sintered body varied widely and the quality stability was poor.

Claims

1. A silicon nitride powder having a β-phase ratio of 98% or more and an amorphous ratio of 1 to 60%.

2. A silicon nitride mixed powder containing an amorphous silicon nitride powder A and a crystalline silicon nitride powder B, 2. The silicon nitride powder according to claim 1, wherein the amorphous silicon nitride powder A is a ball milled product of crystalline silicon nitride powder.

3. 3. The silicon nitride powder according to claim 1 or 2, which is for sintering.

4. A method for producing a silicon nitride sintered body, comprising at least a step of sintering the silicon nitride powder according to claim 3 to obtain a silicon nitride sintered body.

Citation Information

Patent Citations

  • Powdery silicon nitride

    JP1994064907A

  • Silicon nitride powder

    JP1999171512A